2018
DOI: 10.1002/hon.2514
|View full text |Cite
|
Sign up to set email alerts
|

Use of depth of response to predict progression‐free survival in relapsed or refractory multiple myeloma: Evaluation of results from 102 clinical trials

Abstract: Progression-free survival (PFS) is the standard endpoint for demonstration of clinical effectiveness of novel therapies in relapsed or refractory multiple myeloma (RRMM). However, the long evaluation times for PFS limits its usefulness in the development of new therapies. Therefore, the objective of this analysis was to determine the relationship between response rates and median PFS in RRMM. A database was systematically developed from 268 identified RRMM trials reported from 1999 to 2016. Evaluated covariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…stabilization, as evidenced by the prolonged maintenance of existing response compared with placebo. The association of depth of response with improved outcomes is well-established [19][20][21][22] and is supported by the data from TOURMALINE-MM3. In addition, our results showing superior PFS in patients achieving deepening of responses during maintenance are supported by data from other studies, including two separate retrospective analyses that demonstrated both PFS and OS improvements in patients who had a deepening response post-ASCT [3,4].…”
Section: Discussionmentioning
confidence: 58%
“…stabilization, as evidenced by the prolonged maintenance of existing response compared with placebo. The association of depth of response with improved outcomes is well-established [19][20][21][22] and is supported by the data from TOURMALINE-MM3. In addition, our results showing superior PFS in patients achieving deepening of responses during maintenance are supported by data from other studies, including two separate retrospective analyses that demonstrated both PFS and OS improvements in patients who had a deepening response post-ASCT [3,4].…”
Section: Discussionmentioning
confidence: 58%
“…However, the degree of association may be different depending on patient and disease factors, and specific treatments received [ 34 37 ]. A large meta-analysis of data from 102 studies involving 13 322 patients with RRMM indicated a correlation between the rate of VGPR or better and median PFS ( R 2 = 0.63) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, tumor size end points from tumor growth inhibition (TGI) model was used to link exposure and OS in exposure‐TGI‐OS models in an attempt to resolve the confounding effect by baseline prognostic disease marker 56–58 . The association between survival and a short‐term end point such as response rate 59–61 or TGI 58 has been shown in some indications, but more work needs to be done in this direction.…”
Section: Strategies To Mitigate the Confounding Effectmentioning
confidence: 99%